Desempenho produtivo de ovinos confinados submetidos a dietas contendo óleo de buriti e babaçu - SOUSA, Jéssica Maria (2017)
The objective of this research was to evaluate the performance, ingestive behavior and gross profit margin of sheep fed with diets containing buriti and babassu oil. Twenty one sheep castrated were used, ½ Santa Inês x ½ Dorper, with an approximate age of 150 days and an average weight of 18 ± 3 kg at the beginning of the experiment. The animals were distributed in randomized blocks with three treatments and seven repetitions. The trial consisted of 10 days for adaptation and 46 for data collection, totaling 56 days. It was determined by nutrient intake, water intake, weight gain and conversion. The feeding behavior was determined in the last two days of the trial period, by quantification for 24 hours/day. The activities of the evaluated animals were: eating, ruminating and idle. The estimate of economic viability was based on the calculation of the gross profit margin. Insertion of 4% buriti or babassu oil to feedlot sheep finishing influenced (P>0,05) the dry matter intake, consumption of crude protein, neutral detergent fiber consumption, consumption of organic matter and metabolizable energy consumption, however, there was (P<0,05) effect on consumption of ether extract, total carbohydrate consumption and nonfibrous carbohydrate consumption. The inclusion of oils did not affect (P>0,05) weight gain of animals, with an average value of 190.86 g/dia, as well as there was no (P>0,05) influence in general on ingestive behavior..